PASIF PERIFERAL: STRUKTUR ERGATIF DALAM BAHASA INDONESIA - Sry Satriya Tjatur Wisnu Sasangka (Metalingua: Jurnal Penelitian Bahasa, 2016)
UNTIL today, passive voices are characterized by the use of (1) the prefix di-, (2)the prefix ter-, (3) the prefix ke-, and (4) personal pronouns + nonprefixed verb.Number (1) is the original passive form, while number (2), (3), and (4) areperipheral passive forms. Peripheral passive can be distinguished by the form ofanti-active and ergative although they both cannot be reversed into their activevoice. This article will only discuss the ergative from in Indonesian, while thegoal is to describe the form of ergative structure in Indonesian. The method beingused is inferential descriptive method that not only describe the form and thecharacteristics of ergative in Indonesian language but also to analyze it. It isshown that the ergative structure in Indonesian was different from the passivestructure. The original passive structure can be reformed into the active structureas passive form is essentially an elaboration of the active form. However, theergative structure cannot be returned into the active form because the form is notderived from the active structure. The ergative form is dominantly characterizedby the use of personal pronouns + verb without prefix as predicate in the sentence. AbstrakSELAMA ini bentuk pasif ditandai dengan penggunaan (1) prefiks di-, (2) prefiks ter-,(3) prefiks ke-, dan (4) pronominal persona+verba takberprefiks. Bentuk (1)merupakan pasif asli, sedangkan bentuk (2), (3), dan (4) merupakan pasif periferal.Pasif periferal pun dapat dibedakan atas antiaktif dan ergatif meskipun keduanya samasamatidak dapat dikembalikan ke bentuk aktif. Artikel ini hanya membahas bentukergatif dalam bahasa Indonesia, sedangkan tujuannya adalah mendeskripsikan wujudstruktur ergatif dalam bahasa Indonesia. Metode yang digunakan adalah metodedeskriptif inferensial yang bukan hanya memaparkan bentuk dan ciri ergatif dalambahasa Indonesia melainkan juga menganalisis dan menyimpulkannya. Hasilnya diketahuibahwa struktur ergatif dalam bahasa Indonesai ternyata berbeda dengan struktur pasif.Struktur pasif asli dapat dikembalikan ke struktur aktif karena bentuk pasif pada dasarnyamerupakan penjabaran bentuk aktif, sedangkan struktur ergatif tidak dapat dikembalikanke bentuk aktif karena bentuk itu memang tidak diturunkan dari struktur aktif. Bentukergatif lebih dominan ditandai dengan penggunaan pronomina persona + verba tanpaprefiks sebagai predikat kalimat.